The Impact of Gender Equality-Based Learning Programs on Character Building in Undergraduate Midwifery Students: A Cross-Sectional Study in DKI Jakarta - Ichwan, Erika Yulita; Supradewi, Indra; Sari, Gita Nirmala; Wahyuni, Elly Dwi; Oktalia, Juli; Fitriana, Shentya (Women, Midwives and Midwifery, 2025)
Background: Gender inequality significantly affects women's reproductive health and overall well-being. Midwives play a crucial role in addressing these issues through gender-equitable practices. Purpose: This study aims to evaluate the effectiveness of gender equality-based learning programs in shaping the character of undergraduate midwifery students. Methods: A cross-sectional study involving 298 midwifery students in DKI Jakarta was conducted. Data collection used sequential sampling and a validated questionnaire distributed via Google Forms. Logistic regression analyzed associations between students' characteristics and gender-equitable character. Results: Students with poor gender knowledge were 30 times more likely to exhibit gender-inequity characters (OR=30.18, 95% CI=11.40-79.91). Negative attitudes towards gender concepts increased the risk of gender-inequity characters by 44% (OR=1.44, 95% CI=1.05-1.98). A learning environment lacking gender equity doubled this risk (OR=2.83, 95% CI=1.98-4.04). Conclusion: Incorporating gender-equitable concepts and practices into midwifery curricula is essential for developing gender-equitable midwives. This integration could reduce gender disparities and improve health outcomes.